Hubungan Antara Harga Diri Dengan Kecenderungan Narsistik Pada Pengguna Instagram Ditinjau Dari Jenis Kelamin - Bhakti, Annisa Kusuma, Susatyo Yuwono S.Psi, M.Si., Psi (2016)
Social networking has raised new phenomena such as the selfie, also the habit of renewing the image in daily activities that lead to a narcissistic behavior. Narcissistic tendency generally have low self esteem, because of the fall of wishful thinking. The user's connection with the instagram, narcissistic tendencies can help to avoid feeling disappointed. The purpose of this research is to know the relationship between narcissistic tendencies with self esteem on user instagram, a narcissistic tendency difference on instagram users in terms of gender, the level of self-esteem with a narcissistic tendencies, the effective contribution of self-esteem with a narcissistic tendencies. The proposed hypothesis, namely there are negative relationship between narcissistic tendencies with self esteem and there is a difference between a narcissistic tendency on instagram users in terms of gender. The subject in this study amounts to 120 people, the students of the Faculty of psychology of the Muhammadiyah University of Surakarta age 18-24 years of age, have a personal account with the instagram has joined more than six months, active in accessing account instagram (check the notification/notification, check the front page or explore, like, make comments, or upload a photo), has a population of more than 90 photos. The technique of sampling in research this is incidental sampling. Data analysis was done with the analysis of the correlation of product moment and independent sampel t-test using the assistive program SPSS 15.0 For Windows programs. Based on the results of the calculation of the correlation coefficients obtained results rx y =-0.209 with sig = 0.011 (p < 0.05)and based on the results of the t-test test earned value significance 0.118 > 0.05. These results indicate that there is a negative relationship of atnara self-esteem with narcissistic tendencies. Effective contribution (SE) self-esteem against a narcissistic tendency of 4.3%, demonstrated by the determinant of the coefficient (r²) of 0.043. The level of a narcissistic tendency of users to low level while classified as instagram self-esteem belongs to high.